Perencanaan Gedung Kantor Wali Nagari Gurun Di Kecamatan Harau Kabupaten Lima Puluh Kota Provinsi Sumatera Barat - eka, novia anggraeni (Unmuh Babel Press, 2025)
The Gurun Village Head Office, located in Harau District, Lima Puluh Kota Regency, West Sumatra Province, is an infrastructure closely related to public services within the village. Currently, the existing office building is inadequate in terms of the number and area of ​​space, and the building design does not meet operational needs. An office building design that can meet these needs is needed, with efficiency and structural strength being the main priorities. The planning refers to SNI 1727-2020 regarding minimum design loads and related criteria for buildings and other structures. SNI 2847-2019 explains the requirements for structural concrete for buildings, SNI 1726-2019 discusses earthquake resistance planning for building and non-building structures, and SNI 2052-2017 for concrete reinforcement steel. From this planning, the dimensions of the main beam are 35/50 cm, the sub-beam 25/40 cm, the column 50/50 cm, the floor slab thickness 12 cm, and the roof slab 10 cm. Based on the results of the cross-section capacity inspection, it was found that the planned dimensions met the requirements, allowing the design to be implemented for a building that meets structural standards. This design can be used as a reference by the village head when constructing a new office in the future.